Mitos Keris Ki Baru Gajah: Sumber Tekstual Tradisi Pembersihan Keris di Kecamatan Kediri, Tabanan, Bali - Meitridwiastiti, Anak Agung Ayu; Kusuma Atmaja, I Gusti Bagus Agung; Desy Damayanthi, Ni Putu (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
The myth of Keris Ki Baru Gajah as it is written in the text of Purana Pura Luhur Pakendungan, Kediri Subdistrict, Tabanan Regency, Bali, has become the textual source of guideline for cleansing ritual nglisah , which is rubbing oil into the blade of keris being ritualized. This article analyses the myth of Keris Ki Baru Gajah which gives contribution to the culture preservation so that the meaning and purpose of the keris cleansing ritual can be understood and performed continuously. Data were collected by literature review, interview, and recording technique and they were analyzed with the function theory and semiotic. Analysis shows that the myth of the Keris Ki Baru Gajah serves as a guide in the implementation of the tradition of separating. In addition, this myth also functions as a medium for public education, strengthening community social relations, and is believed to be a repellent for plague. The meaning of the myth, namely symbolic meaning, loyalty, and fertility. It is hoped that the tradition derived from a myth can provide harmony and prosperity in the community in Kediri District, Tabanan, Bali. Keywords : nglisah, implemention, function, and meaning